Quality of Life and Risks Associated with Systemic Anti-inflammatory Therapy Versus Fluocinolone Acetonide Intraocular Implant for Intermediate, Posterior or Panuveitis: 54 month results of The Multicenter Uveitis Steroid Treatment (MUST) Trial and Follow-up Study - Kempen, John H. (Ophthalmology, 2015)
PURPOSE: To evaluate the risks and quality of life (QoL) outcomes of fluocinolone acetonide implant versus systemic therapy with corticosteroid and immunosuppression when indicated for intermediate, posterior, and panuveitis. DESIGN: Additional follow-up of a randomized trial cohort PARTICIPANTS: 255 patients with intermediate, posterior or panuveitis, randomized to implant or systemic therapy. METHODS: Randomized subjects with intermediate, posterior, or panuveitis (479 eyes) were followed over 54 months, with 79.2% completing the 54 month visit. MAIN OUTCOME MEASURES: Local and systemic potential complications of the therapies and self-reported health utility, vision-related and generic health-related QoL were studied prospectively. RESULTS: Among initially phakic eyes, cataract and cataract surgery, occurred significantly more often in the implant group (hazard ratio (HR)=3.0, p=0.0001 and HR=3.8, p<0.0001 respectively). In the implant group, most cataract surgery occurred within the first two years. IOP elevation measures occurred more frequently in the implant group (range of HR's=3.7-5.6, all p<0.0001), and glaucoma (assessed annually) also occurred more frequently (26.3% vs. 10.2% by 48 months, HR=3.0, p=0.0002). In contrast, potential complications of systemic therapy including measures of hypertension, hyperlipidemia, diabetes, bone disease, and hematological and serum chemistry indicators of immunosuppression toxicity did not differ between groups through 54 months. Indices of QoL initially favored implant therapy by a modest margin. However, all summary measures of health utility and vision-related or generic health-related QoL were minimally and non-significantly different by 54 months with the exception of the SF-36 physical component summary score which favored implant by a small margin at 54 months (3.17 on a scale of 100, p=0.01, not adjusted for multiple comparisons). Mean QoL results were favorable in both groups. CONCLUSIONS: These results suggest that fluocinolone acetonide implant therapy is associated with a clinically important increased risk of glaucoma and cataract with respect to systemic therapy, suggesting that careful monitoring and early intervention to prevent glaucoma is warranted with implant therapy. Systemic therapy subjects avoided a significant excess of toxicities of systemic corticosteroid and immunosuppressive therapies in the trial. Self-reported QoL measures initially favored implant therapy, but over time the measures converged, with generally favorable QoL in both groups.